The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1080/10640260490521442
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Role of Overeaters Anonymous in Women's Recovery from Bulimia Nervosa

Abstract: This study presents a qualitative analysis of the role of the self-help group Overeaters Anonymous (OA) in the treatment experiences of women with bulimia nervosa. It specifies how various elements of OA facilitate or maintain recovery. Using focus groups and individual interviews, data were collected from 26 women who met the criteria for bulimia nervosa. Data analysis revealed that those participants used five OA skills or strategies. These included: (1) OA meeting attendance and participation, (2) interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…Specifically, the themes in the present study supported previous research on the benefits of spirituality in combating eating disorder symptoms (e.g., Marsden et al, ; Wasson & Jackson, ). Our participants did not endorse findings of previous studies, which discussed the use of spirituality to maintain eating disorder symptoms (e.g., Marsden et al, ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Specifically, the themes in the present study supported previous research on the benefits of spirituality in combating eating disorder symptoms (e.g., Marsden et al, ; Wasson & Jackson, ). Our participants did not endorse findings of previous studies, which discussed the use of spirituality to maintain eating disorder symptoms (e.g., Marsden et al, ).…”
Section: Discussionsupporting
confidence: 86%
“…These findings corresponded well with previous research and theory in the field. The beneficial influence of specific spiritual beliefs upon eating disorder symptoms has been underscored by several studies (Buser & Bernard, ; Forthun et al, ; Marsden et al, ; Wasson & Jackson, ; Watkins et al, ). For example, as noted earlier, individuals who believed that they were close to God/Higher Power during times of stress reported fewer bulimic symptoms (Buser & Bernard, ).…”
Section: Discussionmentioning
confidence: 99%
“…Some positive influences were reported related to a sense of universality and connection, as seen previously (Tozzi et al, 2003;Wasson & Jackson, 2004). Seeing others who had recovered, or conversely, observing those who were "worse off" were forms of vicarious learning (Lamoureux & Bottorff, 2005;Pettersen & Rosenvinge, 2002;Wasson & Jackson, 2004).…”
Section: Discussionmentioning
confidence: 86%
“…Similarly, social connectedness was deemed helpful, consistent with prior research on binge eating disorder in nonathletes (Krentz, Chew, & Arthur, 2005). Finally, as reported by our athletes, spirituality is a factor that assists recovery in nonathletes (D'Abundo & Chally, 2004;Matusek & Knudson, 2009), particularly for those who use the 12-step "Overeaters' Anonymous" recovery program (Wasson & Jackson, 2004).…”
Section: Discussionmentioning
confidence: 90%
“…For example, Wasson and Jackson (2004) conducted focus groups to understand how women with bulimia used OA in their recovery and found that meetings, spirituality, support from a sponsor, writing and food plans were the key elements identified by participants as facilitative. The role of social support in the success of 12-step programs across numerous samples has also been supported in the literature (e.g.…”
Section: Discussionmentioning
confidence: 99%